Pemberdayaan Kader Posyandu dalam Meningkatkan Tumbuh Kembang Balita dengan Media Cetak Buku Saku “Teman Bunda” - Nikmah, Nurun; Qomari, Selvia Nurul; Antina, Rila Rindi (Indonesian Journal of Community Dedication in Health (IJCDH), 2025)
Growth and development are phases that every individual will go through. It is essential to pay attention to factors that can influence the process of growth and development. The success of a toddler’s growth and development depends not only on nutrition but also on the knowledge of those around the toddler. The understanding of the growth and development process will help mothers to be able to maximize the growth and development of their toddlers. Besides, since cadres are the community members tasked with promoting health in the village, they also need to be knowledgeable in this area. One of the efforts to enhance the knowledge of cadres was carried out by providing education using the Buku Saku "Teman Bunda" for 28 cadres in Mlajah Village, Bangkalan District, Bangkalan Regency. The outcomes of community service positively affect cadres' increased level of knowledge. Before the education was provided, there were 16 cadres with a sufficient level of knowledge (57.24%) and and 12 cadres with good knowledge (42.86%). Following the provision of education, the number of cadres with good knowledge increased to 23 people (82.14%), while the number with sufficient knowledge decreased to five (17.86%). The results of this community service indicate an increase in the knowledge of the cadres regarding child development. It is hoped that this increased understanding will enable them to support mothers in the process of optimizing the toddlers’ growth and development.